Application of electrospinning technique in development of intelligent food packaging: A short review of recent trends. Issue 9 (21st July 2020) - Aman Mohammadi, Masoud; Hosseini, Seyede Marzieh; Yousefi, Mohammad
Abstract: Intelligent food packaging refers to packages with the ability to sense foodstuff changes and to inform customers of the packaging content variations. They are often accompanied by smart detecting devices. Providing a suitable platform to include these devices into packaging polymers has always been discussing. Electrospun nanofibers produced through the electrospinning have been recently utilized as an outstanding and novel platforms for this purpose. Thus, the main aim of this study is to investigate recent trends in producing intelligent food packaging using electrospinning technique. In this regard, this paper was categorized into two chief sections, including (a) the principal of electrospinning technique to fabricate fine nanofibers and the parameters affecting the quality of electrospun fibers, and (b) the role of nanofibers as a platform to cover pH indicators in intelligent food packaging.